Предмет: Алгебра, автор: raximjonxasanov13

Помогите на 11
Пожалуйста

Приложения:

Ответы

Автор ответа: alennnkamorozova
1

Ответ:

Объяснение:

1) (×-3)² - (×+2)² = -25

(×-3)² - (×+2)² + 25 = 0

(×-3+×+2)(×-3-×-2) + 25 = 0

(2×-1)(-2) + 25 = 0

-4× + 2 + 25 = 0

-4× + 27 = 0

-4× = -27

× = -27 / -4

× = 6.75

3) (×+2)² - (×-1)²=15

(×+2+×-1)(×+2-×+1)=15

(2×+1)(3)=15

6×+3=15

6×=15-3

6×=12

×=12/6

×=2

4) (×-1)² - (×-2)²=5

(×-1+×-2)(×-1-×+2)=5

(-2×-3)(1)=5

-2×-3=5

-2×=5+3

-2×=8

×=8/-2

×=-4


raximjonxasanov13: Спасибо
Похожие вопросы
Предмет: Алгебра, автор: Аноним